Fears, hopes and the politics of time-space: The media frames of Japan in the Chinese People's Daily. (October 2019) - Guan, Tianru; Liu, Tianyang
Based on a qualitative content analysis of 15 years of media coverage of Japan in the most comprehensive and influential official media, the Chinese People's Daily newspaper, this article argues that the framing of Japan by the People's Daily was produced and rearticulated by the combinations of, and changes in, different geostrategic discourses, referred to in this article as the discourses of 'geopolitical fears' and 'geoeconomic hopes'. These discourses in the framing of Japan by the People's Daily are further rearticulated and reinterpreted in terms of plural constructions of time (progress, decline and cycle). Drawing on a spatio-temporal analytical framework, the article presents a counterargument to the prevailing view that assumes that the framing strategies of China towards Japan are focused on issues of conflict, threat and fear. Rather, the results showed that it was through the alignment and balance of the discourses of geopolitical fears and geoeconomic hopes in a heterogeneous construction of time(s) that the image(s) of Japan emerged in Chinese media.